Efficacy of propranolol in infantile hemangioma (Bangladesh Medical Journal Khulna, 2015)
Hemangiomas, are the most common benign tumors of infancy. Despite their selflimited course, infantile capillary hemangiomas can cause local complications e.g. pain, ulceration, bleeding etc. The usual treatments include oral/intralesional steroids, alpha interferon, cytotoxins, pulsed dye laser and cosmetic surgery resection. These treatments are not free of multiple complications and toxic side effects. We report our experience with the use of propranolol in 2 children with haemangiomas along with review of relevant literature. Both the hemangioma cases promptly responded to low-dose oral propranolol. DOI: http://dx.doi.org/10.3329/bmjk.v47i1-2.22561 Bang Med J (Khulna) 2014; 47 : 32-35